Business Ethics in Turkey: An Empirical Investigation with Special Emphasis on Gender - Ekin, M. G. Serap (Atakan) (Journal of business ethics, 1999)
In today's complex business world, the question of business ethics is increasingly gaining importance as managers and employees face numerous ethical dilemmas in their jobs. The ethical climate in the Turkish business environment is also at a critical stage, and the business community as a whole is troubled by ethical problems. This study attempts to determine the effect of individual, managerial and organizational factors on the ethical judgments of Turkish managers, and to evaluate the ethical perceptions of these managers. The findings of this study reveal that the ethics score, the measure of ethical judgment, of Turkish managers differs significantly only with respect to gender and that female managers have higher ethics score than male managers. Other individual, managerial and organizational factors considered in this study do not have any significant effect on the ethical judgments of the managers. A comparative analysis between female and male managers in terms of their ranking of the eleven ethical business scenarios, ranking of the sixteen unethical acts, ranking of the factors influencing managers to engage in unethical practices, and ranking of the various parties to whom a company is socially responsible enables the researchers to enlighten the subject of business ethics in Turkey.